The Role of Regulatory Arbitrage in U.S. Banks' International Lending Flows: Bank-Level Evidence - Judit Temesvary (FIW - Research Centre International Economics, 2015)
This paper examines how cross-border differences in the stringency of bank regulations affect U.S. banks' international activities. The analysis relies on a unique bank-level dataset on the globally most active U.S. banks' balance sheet as well as their cross-border, foreign affiliate lending and foreign market entry choices in 82 foreign countries in the 2003-2013 period. Results show that U.S. banks are significantly more likely to enter foreign markets with relatively laxer bank capital and disclosure requirements, and exit foreign markets with relatively stricter deposit insurance schemes and more restrictions on activities. Banks substitute away from foreign affiliate lending (via subsidiaries in the foreign country) towards cross-border lending (originating from the U.S.) in foreign countries with more powerful and independent bank regulators and limits on activities.
Keywords: F3; F4; G2; 330; International bank lending; Cross-border regulatory arbitrage; Foreign market entry and exit; Balance sheet effects